Debt to Equity Ratio, Degree of Operating Leverage Stock Beta and Stock Returns of Food and Beverages Companies on the Indonesian Stock Exchange - Lusia Astra Sari; Yanthi R.I. Hutagaol (Journal of Applied Finance & Accounting, 2009)
This research examines three factors that may have relationships with returns on stock investment. The factors tested under this research are three types of risk associated with a company’s capital structure, company’s business risk, and market risk of the company’s stock. A company’s capital structure is measured by debt to equity ratio, a company’s business risk is measured by degree of operating leverage, while the market risk of the company’s stock is measured by stock beta. This research focuses on the food and beverages (F&B) industry. The sample firms are F&B firms that are listed on the Indonesian Stock Exchange in the period of 2003-2008. The results show that there is a positive relationship between debt to equity ratio and stock return; however this result is insignificant statistically. A similar result is found between the degree of operating leverage and stock return. There is a positive significant relationship between the stock beta and stock return. The result also shows that debt to equity ratio, degree of operating leverage, and stock beta all together do not have a significant influence on the stock returns of food and beverage companies on the Indonesian Stock Exchange during 2003-2008.